PENGARUH SALURAN DISTRIBUSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK ALAT KESEHATAN MEREK OMRON PADA PT. SUMBER MEDIKA INDONESIA MEDAN (DISTRIBUTOR ALAT KESEHATAN) - Felicia Wijaya; Andy Andy; Vincent Vincent; Steven Steven; Rahmat Alamsyah Harahap (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This research aims at finding the effect of (1) distribution channels for purchasing decisions, (2) service quality for purchasing decisions, (3) distribution channels and service quality on purchasing decisions. The research method is a quantitative approach, a type of quantitative descriptive research in which it is explanatory research. Techniques of collecting data are by having interview, questionnaire and documentation study. Data analysis method is multiple linear regressions by testing the classical assumptions of normality, multicollinearity and heteroscedasticity. The population of this research is 232 customers, samples were taken by simple random sampling, as many as 147 customers and 30 customers were tested both validity and reliability. Research findings show that simultaneous distribution channels and service quality (Test F) have a positive effect on purchasing decisions with a value of 18,568. Partially (Test t) distribution channels have a positive and significant effect with a value of 2.802 and service quality has a positive and significant effect with a value of 2.963 on purchasing decisions. The test results of the coefficient of determination (R Square) obtained Adjusted R Square of 0.194 means that the distribution channels and service quality affect the purchasing decisions with a percentage level of 19.4% while the remaining 80.6% are other factors that were not examined by researcher.